Reading and writing scenes in History classes.A look at the secondary level classrooms in the city of Tandil (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
This paper tries to explore different aspects that occur in reading and writing history in secondary school. Some of the questions that guide this work are:  which are the reading and writing practices that teachers performed in order to reach good aims with their students? Which are the perceptions underneath there practices? This search tries to put on surface the goals of the history of reading and the social sciences in relation with the idea that the motor of change in the scholar system are the teachers and the students. Also our methodological work is based on ethnography because it allows contemplating the everyday of the scholar rooms. This kind of work reveals that commonly the teachers tries to read the texts in class. The teachers mix different activities as reading in out loud, discussion themes and writing on the board. These practices stimulate different questions in relation with the history contents of the class. As searchers we propose some clues to analyze these activities.
Keywords: teaching history; practices; teachers; reading; writing